2010
DOI: 10.2298/abs1001075t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cisplatin on lipid peroxidation and the glutathione redox status in the liver of male rats: The protective role of selenium

Abstract: The role of oxidative stress in cisplatin (CP) toxicity and its prevention by pretreatment with selenium (Se) was investigated. Male Wistar albino rats were injected with a single dose of cisplatin (7.5 mg CP/kg b.m., i.p.) and selenium (6 mg Se/kg b.m, as Na2SeO3, i.p.) alone or in combination. The results suggest that CP intoxication induces oxidative stress and alters the glutathione redox status: reduced glutathione (GSH), oxidized glutathione (GSSG) and the GSH/GSSG ratio (GSH RI), resulting in increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The depletion of GSH is also believed to be related to perturbation of intracellular calcium homeostasis by the increased cytosolic calcium which can lead to oxidative stress and cell injury (Pereira and de Oliveira, 2000). A decrease in cellular GSH concentration has been inversely correlated with lipid peroxidation in the liver (Trbojevic et al, 2010). It has been reported that the alterations induced by cisplatin in the tissues (particularly liver and kidney) were characterized by signs of injury such as increase of LPO products and changes in GSH levels (Naziroglu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of GSH is also believed to be related to perturbation of intracellular calcium homeostasis by the increased cytosolic calcium which can lead to oxidative stress and cell injury (Pereira and de Oliveira, 2000). A decrease in cellular GSH concentration has been inversely correlated with lipid peroxidation in the liver (Trbojevic et al, 2010). It has been reported that the alterations induced by cisplatin in the tissues (particularly liver and kidney) were characterized by signs of injury such as increase of LPO products and changes in GSH levels (Naziroglu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, several hypotheses have been put forward to explain CP-induced toxicity, the most notable of which is oxidative stress [4]. Research has indicated that CP toxicity in tissues is associated with increases in malondialdehyde (MDA), a byproduct of polyunsaturated fatty acid peroxidation, and reactive oxygen species (ROS) such as hydrogen peroxide (H 2 O 2 ) [5]. Additional-ly, CP has been found to reduce the activity of antioxidants like superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), and glutathione S-transferase (GST), which represent a defense system against free radical damage [6,7].…”
Section: Introductionmentioning
confidence: 99%